An Analysis of Reading Comprehension Questions in English Textbooks Bahasa Inggris Work in Progress and Pathway to English Based on Barrett’s Taxonomy - Novita Rahmadani; Yetti Zainil (Universitas Negeri Padang, 2023)
This descriptive qualitative research aimed to find out the cognitive levels of reading comprehension questions found in English textbooks “Bahasa Inggris Work in Progress” and “Pathway to English” and to investigate English teachers’ opinions on the cognitive levels of Barrett’s taxonomy. There are five levels in this taxonomy which are literal comprehension, reorganization, inferential comprehension, evaluation, and appreciation. The instruments of this research were a checklist table and a semi-structured interview. The result of the analysis showed that there were 117 questions (27%) for the literal comprehension level, 98 questions (22%) for the reorganization level, 176 questions (40%) for inferential comprehension level, 25 questions (6%) for evaluation level, and 21 questions (5%) categorized into appreciation level. The percentages of cognitive levels in the textbooks did not meet the recommended proportion. From the interview result, it was found that the English teachers considered Barrett’s taxonomy as the suitable and practical framework to analyse the cognitive levels of reading comprehension questions. The teachers also stated that Barrett’s taxonomy aligns with Merdeka’s curriculum objectives.